L’anticommunisme, l’autre moteur de Jean-Marie Le Pen - Adrian Thomas (Cahiers d’histoire.)
Retrospectives on Jean-Marie Le Pen highlight his most infamous statements, but almost systematically overlook a central aspect of his commitment: anti-communism. This is crucial because it is a cardinal point of the far right, inseparable from the global struggle to preserve a white Western civilization. In fact, anti-Marxism has often been the common denominator of reactionary groups, and Le Pen is its best incarnation. Throughout his career, whether in Vietnam or in the Palais Bourbon, Le Pen was convinced that he was fighting Bolshevism and its avatars tooth and nail, be they student trade unionists, Algerian independence fighters or militants of the left-wing union in all its plurality. Le Pen never lost sight of the main objective of destroying the PCF and the USSR, the supreme enemies. Without claiming to be exhaustive, here is a look back at 75 years of hate for the red.